2017
DOI: 10.1038/mp.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

A paternal methyl donor-rich diet altered cognitive and neural functions in offspring mice

Abstract: Dietary intake of methyl donors, such as folic acid and methionine, shows considerable intra-individual variation in human populations. While it is recognized that maternal departures from the optimum of dietary methyl donor intake can increase the risk for mental health issues and neurological disorders in offspring, it has not been explored whether paternal dietary methyl donor intake influences behavioral and cognitive functions in the next generation. Here, we report that elevated paternal dietary methyl d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 64 publications
2
48
1
Order By: Relevance
“…As in studies of poor maternal diet during pregnancy, we observed that the enhanced foetal growth programmed by paternal LPD was associated subsequently with increased adiposity, impaired glucose metabolism, hypotension and vascular dysfunction in adult offspring (Watkins & Sinclair 2014). Separately, other studies have shown significant changes in foetal (Carone et al 2010, Lambrot et al 2013 and postnatal offspring development and metabolic health (Anderson et al 2006, McPherson et al 2016, Ryan et al 2018 in response to paternal diet or food intake in mice. Interestingly, recent studies have demonstrated robust transgenerational effects of chronic paternal stress on offspring well-being and hypothalamic pituitary adrenal axis function (Gapp et al 2014, Rodgers et al 2015.…”
Section: Journal Of Endocrinologysupporting
confidence: 65%
“…As in studies of poor maternal diet during pregnancy, we observed that the enhanced foetal growth programmed by paternal LPD was associated subsequently with increased adiposity, impaired glucose metabolism, hypotension and vascular dysfunction in adult offspring (Watkins & Sinclair 2014). Separately, other studies have shown significant changes in foetal (Carone et al 2010, Lambrot et al 2013 and postnatal offspring development and metabolic health (Anderson et al 2006, McPherson et al 2016, Ryan et al 2018 in response to paternal diet or food intake in mice. Interestingly, recent studies have demonstrated robust transgenerational effects of chronic paternal stress on offspring well-being and hypothalamic pituitary adrenal axis function (Gapp et al 2014, Rodgers et al 2015.…”
Section: Journal Of Endocrinologysupporting
confidence: 65%
“…Thus, it has been reported that maternal vitamin C deficiency does not affect embryonic development but is known to cause a reduction in the number of germ cells in the fetus and reduced fertility in adulthood [77]. As for paternal effect, it has also been reported that children whose fathers consumed a diet rich in methyl-donor molecules have altered cognitive and neurological functions [78]. Additionally, mouse pups from fathers eating a diet deficient in folic acid showed a high incidence of congenital anomalies [79].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, offspring of males that are fed a low‐protein diet during the post‐weaning period have altered DNA methylation within the peroxisome proliferator‐activated receptor alpha ( Pparα ) gene in hepatic tissue (Carone et al, ). In Agouti mice, prenatal exposure to a high methyl donor diet has been demonstrated to impact DNA methylation resulting in dramatic phenotypic changes (Morgan, Sutherland, Martin, & Whitelaw, ) and these epigenetic effects can also be observed in the offspring of male mice placed on a high methyl donor diet prior to mating (Ryan et al, ). Thus, pre‐mating male diet can induce epigenetic changes in tissues and gene targets that shape metabolic outcomes in offspring (also see Dunford & Sangster, ).…”
Section: Paternal Epigenetic Effects In Offspringmentioning
confidence: 99%